Kadar hs-CRP pada Pasien DM tipe-2 Dengan dan Tanpa Hipertensi - Efi Ramadhan; Ozar Sanuddin; Dharma Lindarto (Fakultas Kedokteran USU, 2016)
Introduction : More than 50% of patients with type-2 diabetes have hypertension. Hypertension contributes the development of cardiovascular disease. hs-CRP is an inflammation marker which is associated with cardiovascular risk. The aim of this study is to measure hs-CRP in type-2 diabetes with and without hypertension and to assess hs-CRP levels based on cardiovascular risk group.Methods : This study is an analytical observational cross-sectional study. Performed at the Department of Clinical Pathology Adam Malik Hospital, the total of type-2 DM subjects with and without hypertension is 56, with 28 in each group. Laboratory tests: complete blood count, blood sugar levels, HbA1C, SGOT, SGPT, Lipid Profile, hs-CRP.Results : There was significant differences in the average levels of hs-CRP in type-2 diabetic patients with hypertension (4.03±2.49) and without hypertension (1.98 ± 1.93), p = 0.001. In this study seen an increase in the average levels of hs-CRP is based on group risk of cardiovascular disease in patients with type 2 diabetes with and without hypertension (p= 0,001 ). In the group of type-2 diabetes with hypertension, may not find a mild risk of cardio-vascular disease. It shows the type 2 DM patients with hypertension is more at risk of cardio-vascular disease than type 2 DM without hypertension.Discussion : hs-CRP levels were higher in type-2 diabetes with hypertension and associated with the risk of cardiovascular disease. Conclusion : There are significant differences between the levels of hs-CRP type-2 diabetes with and without hypertension.Keywords : type-2 diabetes, hypertension, hs-CRP